Ґрунтові поховання культури шнурової кераміки на території українського Прикарпаття - Войтович, М.М. (Сіверщина в історії України, 2020)
У статті проаналізовано ґрунтові поховання культури шнурової кераміки у Верхньому Придністер’ї, які є рідкісними серед фунеральних пам’яток цієї культури у регіоні; більшість з них представлена курганними захороненнями. На сьогодні до ґрунтових
поховань належать п’ять досліджених захоронень у Сідому, Березці,
Дем’янові та Бовшеві. Поховання здійснювались в ямах овальної
або прямокутної форми. У Бовшеві та Дем’янові контури ям не
простежені. На дні ям лежали скорчені скелети на лівому чи правому боці без чіткої орієнтації за сторонами світу. У Сідому слідів скелета не простежено. У всіх похованнях виявлено супровідний
інвентар, який складався переважно із глиняного посуду, рідше – з
крем’яних знарядь. У похованні 1 в Березці збереглися кістяні підвіски. Також досліджено супровідний матеріал захоронень та наведено аналогії серед речових комплексів синхронних груп і культур. The article focuses on the ground burials of Corded ware culture in
Upper Dnister region, which are quite rare among funeral sites of this
culture in the region. Most of them are represented by barrows. According
to present data, five burials researched in Side, Berizka, Demianiv and
Bovshiv are belonged to ground burials. First ground burials of CWC in
the region were discovered in 1962–1963 by V. Baran during research
in Demianiv and Bovshiv. Two ground burials were recorded in 1981 by
V. Cyhylyk near Berezets. The last site was discovered in 1996 near the
village of Side. Ground burial in Upper Dnister region is characterized
by crouched pose of buried person (in four burials). In one case, the
skeletal remains were not preserved due to the aggressive conditions
of the local soil (Side). In two cases the skeletons lay on the right side
(Bovshiv, Demianiv), in two cases – on the left (Berezets). There is no
clear spatial orientation of the skull. In no case gender of the buried is
identified. In two cases, no traces of the burial pit were found (Bovshiv,
Demianiv). Two buried objects in Berezets had an oval shape. Burial pit
in Side had a rectangular shape, with rounded corners. In all cases, the
burial inventory included ceramic ware, represented by goblets, amphorae
and a bowl. Quite often there are also flint products. In two burials bone
products appeared, represented by decorations (Berezets, burial 1) and
tools (Demianiv). On the basis of analysis of the burial inventory from
the graves, close connection of the material culture with the sites of the
western groups of CWC was established. For the ceramic goblet from Side,
direct analogies were found at the sites in Poland and Belarus. It is also
established that the burials from Berezets belong to the group of early
sites of CWC, which is indicated by ceramic complex and bone pendants,
which are found on the sites of Małopolska along with ceramic ware,
shape of which is close to products of type A. Instead, other ground burials
represent the late stage. Thus, Bovshiv burial amphora belongs to the
type IIc vessels according to classification scheme developed by J. Machnik,
which are recorded exclusively in the burials of the late stage of CWC.